Point Clipping Algorithm on Employee Presence Application for Geolocation of Employee Position - Rahmatulloh, Alam; Rianto, Rianto; Shihab, Muhammad Quraish (Universitas Muhammadiyah Malang, 2019)
In organizations, companies or agencies such as the Office of Communication and Information Technology, presence has become one of the critical things in assessing the performance of workers/employees. There are several ways to do attendance, where one of them can facilitate the present process with digital tools/machines such as smartphones that utilize the GPS feature to run APIs such as Google Geolocation on Android. Also, a system is needed that can manage the results of the present process, such as web-based applications that can also be accessed through either a computer or smartphone. Therefore, the need to build a presence application both in the presence and in management that can help agencies such as Office of Communication and Information (Diskominfo) to handle internal processes, especially in the management of its employees. In this study, the application in the construction of its application is used Point Clipping algorithm as a tool for the present process that can take advantage of the GPS feature. Based on the results of the tests conducted, the accuracy value of the incoming and returning attendance process was obtained in the location area with an average of each side of the area of approximately 11.21 meters at the entry point and 18.05 meters at the presence of going home outside the office, where the location area boundary outside the specified office which is around 15 meters and the time test is obtained the time delay value in the attendance process with an average of each side of the area of about 9.6 seconds at the incoming attendance and 8.3 seconds at the home attendance.